The impact of the circular house shape strategy on the achievement of fifth grade literary students in the subject of literature and texts (Journal of the College of Basic Education, 2022)
The current research aims to identify "the effect of the strategy of the circular house shape in the collection of literature and texts for fifth grade literary students.To achieve this, the researcher relied on an experimental design with partial control, which is the design of the control group with a post-test only. The researcher chose a sample of (82) female students from the fifth literary grade in Al-Huda Prep for Girls affiliated to the General Directorate of Education of Baghdad / Al-Rusafa Al-Awwal, and they were distributed randomly In two groups, consisting of (43) students in the experimental group, and (39) students in the control group, the researcher taught the experimental group using the circular house strategy, and the control group using the traditional method.